Biomechanical properties of polyvinyl alcohol hydrogel as a nucleus pulposus replacement in intervertebral disc herniation: A systematic review - Eko Agus Subagio, Eko (Spandidos Publications, 2023)
The best artificial disc material must closely resemble the viscoelasticity, biomechanics and bioavailability of a natural human intervertebral disc. Currently, there is a lack of reviews discussing the characterization of polyvinyl alcohol (PVA) hydrogel as a nucleus pulposus (NP) replacement in intervertebral disc herniation. The present study systematically reviewed the biomechanical characterization of PVA hydrogel as a potential ideal candidate for the replacement of NP. The PubMed, Google Scholar, Science Direct, and Cochrane Database of Systematic Reviews databases were searched according to the Preferred Reporting Items for Systematic Reviews and Meta‑Analyses guideline. Data from the literature regarding study design, sample size, materials and biomechanical properties were collected. The literature search identified seven publications, which were read to obtain information about the biomechanical characteristics of PVA hydrogel material used with different compounds. Stress, strain and Young's modulus testing outcomes were all evaluated. The biomechanical characteristics of the materials were evaluated to determine how closely they resemble those of the NP. The results revealed that the PVA hydrogel and NP share similar biomechanical characteristics. In order to enhance its biomechanical capabilities, the PVA hydrogel may be combined with other materials.